Metabolism of exogenous ketones - Stubbs, B (2016)
As metabolic substrates, ketone bodies provide an alternative to glucose in order to pro- long survival during starvation. A low carbohydrate, high fat diet can be used to promote ketogenesis without fasting, but long-term compliance can be difficult. Dietary ketone bod- ies may be an alternative method to induce ketosis, so the aim of the work in this Thesis was to investigate the metabolism of exogenous ketones. In the first experimental Chap- ter, the effects of ketone ester and salt drinks on blood β-hydroxybutyrate (βHB), glucose, lipids, electrolytes and pH were determined in healthy humans at rest. Blood D-βHB levels were higher following ketone ester drinks, but it was found that total βHB levels with ke- tone salts were similar, as over 50% of βHB delivered in the salt was the L-isoform, which was only slowly removed from the blood. Circulating glucose and lipid concentrations fell following both ketone drinks. Blood pH fell following ketone ester consumption, but rose following ketone salt drinks, whilst both compounds raised blood sodium and chloride, and lowered potassium. Work in the second Chapter investigated the repeatability of ketone es- ter metabolism with food, successive drinks or continuous nasogastric (NG) infusion. Peak D-βHB levels were repeatable between- and within- subjects at rest but were lower after a meal, although blood acetoacetate, breath acetone and urine βHB were unaffected by feed- ing. βHB kinetic parameters were not altered by existing hyperketonemia from successive ketone ester drinks and total βHB uptake was identical when isovolumetric amounts of ketone ester were continuously infused through a NG tube. The third Chapter explored side-effects of ketone drinks: ketone ester drinks decreased appetite compared to isocaloric dextrose; which may have been linked to effects of βHB on enteroendocrine cells. Fur- thermore, both ester and salt drinks were found to be unpalatable, and to cause a few, mild gastro-intestinal effects that increased with intake. As exogenous ketones could be a per- formance enhancing supplement in sport, the fourth Chapter used a survey to investigate supplement use by endurance athletes. The results demonstrated widespread supplement use, which was highest at the elite level. In the final Chapter, the effect of glycogen lev- els on the oxidation of βHB was determined in isolated perfused rat hearts. Low cardiac glycogen levels decreased βHB oxidation and levels of the intermediates of glycolysis and the Krebs cycle, whilst increasing muscle amino acid levels, suggesting that low glycogen may have impaired anaplerosis. In conclusion, this work extends current understanding of the novel physiological ketosis that occurs following exogenous ketone consumption.